Portraying Metacognitive Awareness Skills of Senior Year College Students: Survey Study - Farani, Rizki; Taufiqurrahman, Baikuni; Azis, Mita Farani (IJELR: International Journal of Education, Language, and Religion, 2024)
Prior researches regarding metacognitive awareness had been conducted but none of them analyzed particularly only to the metacognitive awareness and the senior year of university students. Thus, the aim of this study is to map metacognitive awareness skills of senior year college students at the English Language Education Department. There were 90 students who participated in this survey study. In order to assess their metacognitive awareness skills, this study employed Metacognitive Awareness Inventory (MAI) from Schraw & Dennison (1994), consisted of 52 items, divided into 8 domains: declarative knowledge, procedural knowledge, conditional knowledge, planning, information management strategies, monitoring, debugging strategies, evaluation. The data were analyzed by using a descriptive quantitative method to determine the highest and the lowest domain that represented respondents’ metacognitive awareness. The results showed that the highest metacognitive awareness skill of senior year students was planning ( = 4.02), followed by procedural knowledge (= 3.99), monitoring (= 3.91), information management strategies (= 3.88), declarative knowledge (= 3.87), evaluation ( = 3.85), debugging strategies ( = 3.83), and the lowest domain was conditional knowledge (= 3.81). The findings implied that senior year students could determine goals before starting their learning process. They knew how to achieve their goals, monitored their process, managed information, obtained knowledge, analyzed their performance, and revised their process based on analysis. However, they needed to improve their skill in selecting effective strategies based on specific circumstances.